Validitas Perangkat Pembelajaran Fisika Berbasis Model Generatif Berbantuan Laboratorium Virtual - Shinta Mutiara Dewi; Gunawan Gunawan; Susilawati Susilawati; Ahmad Harjono (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
The purpose of this study is to determine the validity of a learning tools based generative model with virtual laboratory. This type of research is Research & Development refers to the 4-D model which consists of four stages of development, namely define, design, develop and disseminate. Learning tools developed in the form of syllabus, RPP, LKPD, and evaluation instruments.ÃÂ  This paper only focused on the process of testing the validation of the contents and constructs of the learning tool. Validation has been carried out by experts using a validity test instrument in the form of a questionnaire. Validity test for syllabus, lesson plan, student worksheet and evaluation instruments get results with valid categories. Based on the results and discussion of the research it can be concluded that this learning tool is feasible to be used in physics learning.